1994
DOI: 10.1002/gcc.2870110402
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome analysis of brain tumors in childhood

Abstract: We performed a chromosome analysis of 26 pediatric brain tumors, including 20 primitive neuroectodermal tumors (PNETs). 5 astrocytomas, and 1 immature teratoma. Specimens were treated with collagenase, placed in overnight or short-term cultures, and harvested for chromosome analysis. Numerical and/or structural abnormalities were noted in 14 of the 20 PNETs and 4 of the 5 astrocytomas. In 13 PNETs, so-called medulloblastoma in the cerebellum, an i(17q) was the most frequent structural abnormality, accounting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Because of difficulties in generating adequate metaphases, cytogenetic data in these tumour types are still limited. The most frequent abnormality is isochromosome i(17q), found in approximately 30% of cases analysed with conventional cytogenetics (Bigner et al, 1988;Griffin et al, 1988;Biegel et al, 1989;Karnes et al, 1992;VagnerCapodano et al, 1992;Neumann et al, 1993;Fujii et al, 1994). This high incidence of i(17q) was confirmed in a molecular cytogenetic study, which also showed deletions of 17p in 44% of patients (Biegel et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of difficulties in generating adequate metaphases, cytogenetic data in these tumour types are still limited. The most frequent abnormality is isochromosome i(17q), found in approximately 30% of cases analysed with conventional cytogenetics (Bigner et al, 1988;Griffin et al, 1988;Biegel et al, 1989;Karnes et al, 1992;VagnerCapodano et al, 1992;Neumann et al, 1993;Fujii et al, 1994). This high incidence of i(17q) was confirmed in a molecular cytogenetic study, which also showed deletions of 17p in 44% of patients (Biegel et al, 1995).…”
mentioning
confidence: 99%
“…A very recent deletion mapping study localized a common chromosomal disruption within a more centromeric region, at 17p11.2 (Scheurlen et al, 1997). Other recurrent abnormalities have been described, including structural aberrations of chromosomes 1, 3, 6, 11, 16 and X, loss of chromosome 22 and gains of chromosomes 6 and 8 (Farwell et al, 1977;Bigner et al, 1988Bigner et al, , 1990Griffin et al, 1988;Callen et al, 1989;Karnes et al, 1992;Neumann et al, 1993;Fujii et al, 1994). Few gene amplifications have been reported, involving MYC, MYCN or EGFR (Rouah et al, 1989;Wasson et al, 1990;Fuller and Bigner, 1992;Badiali et al, 1995), and more recently the 5p15 and 11q22 chromosomal regions (Reardon et al, 1997).…”
mentioning
confidence: 99%
“…Whereas ependymomas occur in both children and adults, subependymomas and myxopapillary ependymomas are more common in adults. 267 The CGAP website identifies 106 ependymoma karyotypes 1,22,50,62,64,83,92,117,161,175,207,209,225,227,257,270,278,281,293,294 (also reviewed by Mazewski,et al 161 ). The karyotypes described are predominantly normal, and when abnormal are near-diploid, and are characterized by gains and losses of entire chromosomes.…”
Section: Neurosurg Focus / Volume 19 / November 2005mentioning
confidence: 99%
“…The CGAP website combines the two major subgroups, yielding 185 cases. 13,[22][23][24]28,30,50,83,92,175,225,232,278,282 More than 75% of the karyotypes are diploid or near-diploid, with the remaining 25% tetraploid and triploid. Whole chromosomal gains and losses are common and include gains of 1, 3, 4, 6, 7, 8, 17, and 18 and losses of 9, 10, 12, 13, and 19.…”
Section: Tumors With Neuroblastic or Glioblastic Elements (Embryonal mentioning
confidence: 99%
See 1 more Smart Citation